Going the Extra (Synaptic) Mile: Excitotoxicity as the Road Toward Neurodegenerative Diseases - Armada-Moreira, Adam; Gomes, Joana I.; Pina, Carolina Campos; Savchak, Oksana K.; Gonçalves-Ribeiro, Joana; Rei, Nádia; Pinto, Sara; Morais, Tatiana P.; Martins, Robertta Silva; Ribeiro, Filipa F.; Sebastião, Ana M.; Crunelli, Vincenzo; et al. (Frontiers in Cellular Neuroscience, 2020)
Excitotoxicity is a phenomenon that describes the toxic actions of excitatory neurotransmitters, primarily glutamate, where the exacerbated or prolonged activation of glutamate receptors starts a cascade of neurotoxicity that ultimately leads to the loss of neuronal function and cell death. In this process, the shift between normal physiological function and excitotoxicity is largely controlled by astrocytes since they are able to control the levels of glutamate on the synaptic cleft. This control is achieved through glutamate clearance from the synaptic cleft and its underlying recycling through the glutamate-glutamine cycle. The molecular mechanism that triggers excitotoxicity involves alterations in glutamate and calcium metabolism, dysfunction of glutamate transporters, and malfunction of glutamate receptors, particularly NMDAR. On the other hand, excitotoxicity can be regarded as a consequence of other cellular phenomena, such as mitochondrial dysfunction, physical neuronal damage, and oxidative stress. Regardless, it is known that the excessive activation of NMDAR results in the sustained influx of calcium into neurons and leads to a number of deleterious consequences, including mitochondrial dysfunction, reactive oxygen species overproduction, impairment of calcium buffering, release of pro-apoptotic factors, among others, that inevitably contribute to neuronal loss. A large body of evidence implicates NMDAR-mediated excitotoxicity as a central mechanism in the pathogenesis of many neurodegenerative diseases, including amyotrophic lateral sclerosis, Alzheimer’s disease, and epilepsy. In this review, we explore different causes and consequences of excitotoxicity, discuss the involvement of NMDAR-mediated excitotoxicity and its downstream effects on several neurodegenerative disorders, and identify possible strategies to study new aspects of these diseases that may lead to the discovery of new therapeutic approaches. With the understanding that excitotoxicity is a common denominator in neurodegenerative diseases and other disorders, a new perspective on therapy can be considered, where the targets are not specific symptoms, but the underlying cellular phenomena of the disease.